Амвросіївське кістковище бізонів та особливості його використання - Кротова, О.О. (Археологія і давня історія України, 2020)
У статті узагальнено матеріали багаторічних досліджень Амвросіївського кістковища бізонів, сучасний аналіз яких дозволяє внести корективи у деякі спірні питання його інтерпретації. The Amvrosiivka Upper Palaeolithic complex, composed of a camp site and nearby bison bone bed is located in the Donetsk oblast’, at the top of the Kazenna ravine, a right tributary of the Krynka river, which drains into the Mius river. The site is dated by an average of 19000—18000 uncal BP and belong to Epigravettian tradition. The results of the long-term research the Amvrosiivka bison bone bed was analyzed in the article. The features of topography (a gully-terrace on board of a ravine), planigraphy, stratigraphy of a bone bed (the ledges-thresholds and some sterile layers in cultural remains distribution), and also the seasons of the kill of animals (alternative, with prevalence of cold) was summarized. Data about the bison bones (Bison priscus, MNI = 650 and bones with cultural modifications) is presented. The prevalence of the hunter projectile weapon details (27 bone points and about 90 flint micropoints-inserts), and also flint tools for butchering animals among the archaeological finds is determined. The interpretation of the bone bed at the same times was controversial: as a refuse dump near dwelling (Evseev), as a resulted from a one-time (Pidoplichko) or repeated (Efimenko) mass drive of bison, or as a ritual locale (Boriskovskij). At present the site is interpreted as a place of numerous mass drive of bison and, mainly, primary butchering of hunting bag, and also, probably, storages of meat products in the form of the frozen carcasses of bison in a cold season (Krotova, Snizhko, Julien). The ethnoarchaeological data about methods of collective kills by Paleoindian and Indian pedestrian hunters on bison of the North America (Frison 2004) for the reconstruction of possible variants of the mass drive of bison in Amvrosiivka is used. The conclusion is made that for the purpose organization of the series of mass drive of bison at different seasons the hunters in Amvrosiivka used a natural trap — the gully-terrace on a board of ravine — the right tributary of a Kazenna ravine. This terrace with one abrupt and rather high (4—5 m) board, obviously, used for a drive of bison from above, a plateau (method of «jump») that the hunters, obviously, at a certain stage having added with the restraining structure (pens) which should keep the escaped and wounded animals. The variant of a possible shelter from below, a thalweg of the Kazenna ravine (an «arroyo trap» method) also is not excluded.